Aberrant choroid plexus formation drives the development of treatment-related brain toxicity - Bender, Tamara; Schickel, Esther; Schielke, Celine Katharina; Debus, Jürgen; Grosshans, David; Durante, Marco; Schroeder, Insa (Communications biology, 2025)
Brain tumors are commonly treated with radiotherapy, but the efficacy of the treatment is limited by its toxicity to the normal tissue including post-irradiation contrast enhanced lesions often linked to necrosis. The poorly understood mechanisms behind such brain lesions were studied using cerebral organoids. Here we show that irradiation of such organoids leads to dose-dependent growth retardation and formation of liquid-filled cavities but is not correlated with necrosis. Instead, the radiation-induced changes comprise of an enhancement of cortical hem markers, altered neuroepithelial stem cell differentiation, and an increase of ZO1+/AQP1+/CLDN3+-choroid plexus (CP)-like structures accompanied by an upregulation of IGF2 mRNA, known to be expressed in CP and cerebrospinal fluid. The altered differentiation is attributed to changes in the WNT/BMP signaling pathways. We conclude that aberrant CP formation can be involved in radiation-induced brain lesions providing additional strategies for possible countermeasures.
Gesehen am 19.08.2025